2015
DOI: 10.1093/mnras/stv1695
|View full text |Cite
|
Sign up to set email alerts
|

A lower fragmentation mass scale in high-redshift galaxies and its implications on giant clumps: a systematic numerical study

Abstract: We study the effect of sub-grid physics, galaxy mass, structural parameters and resolution on the fragmentation of gas-rich galaxy discs into massive star forming clumps. The initial conditions are set up with the aid of the ARGO cosmological hydrodynamical simulation. Blast-wave feedback does not suppress fragmentation, but reduces both the number of clumps and the duration of the unstable phase. Once formed, bound clumps cannot be destroyed by our feedback model. Widespread fragmentation is promoted by high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
141
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(164 citation statements)
references
References 106 publications
22
141
1
Order By: Relevance
“…While some simulations (Tamburello et al 2015) may imply little importance in the role clumps play in galaxy evolution, observational studies such as this work imply otherwise. Our results, although applicable to UV-selected clumps only, are significant.…”
Section: Discussionmentioning
confidence: 73%
“…While some simulations (Tamburello et al 2015) may imply little importance in the role clumps play in galaxy evolution, observational studies such as this work imply otherwise. Our results, although applicable to UV-selected clumps only, are significant.…”
Section: Discussionmentioning
confidence: 73%
“…This interpretation is further reinforced when looking at the typical stellar masses of clumps. We find that for those two-clump sys-tems with at least one bright component, the majority (∼ 77%) have stellar masses greater than log(M /M ) > 9 a limit beyond which clumps induced by VDI are not observed in simulations (see e.g., Elmegreen et al 2009;Guo et al 2012;Tamburello et al 2015;Bournaud 2016). On the other hand, ∼ 55% of clumps in multi-clump systems have stellar masses lower than log(M /M ) < 9, which might likely result from VDI as well as minor mergers.…”
Section: Clump Stellar Massesmentioning
confidence: 87%
“…This limitation raises the question whether an observed clump is actually a single object or blending of a few nearby smaller clumps. For example, Tamburello et al (2015) argued that many of the giant clumps (with M M 10 8 * >  ) identified in observations are not due to in situ formation but are the result of the blending of smaller structures due to the low resolution of the observations. Similarly, Dessauges-Zavadsky et al (2017a) claimed that the clump masses observed in non-lensed galaxies with a limited spatial resolution of ∼1 kpc are artificially increased due to the clustering of clumps of smaller mass.…”
Section: A Challenge Of Clump Studies and The Motivation Of This Papermentioning
confidence: 99%